PENGARUH INTENSITAS MENGAKSES AKUN TWITTER @FWBESS DAN INTENSITAS KOMUNIKASI ANTAR TEMAN TENTANG SEKS TERHADAP TINGKAT PENERIMAAN SEKS PRANIKAH DI KALANGAN MAHASISWA - Raihan Atha Naufal Wardhana; Sunarto Sunarto; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The presence of peers and social media tends to shape respondents' more positive views regarding premarital sexual behavior. This study aims to see the effect of the intensity of accessing the @FWBESS Twitter account and the intensity of communication between friends about sex towards the level of acceptance of student premarital sex. The theory used is uses and gratification explained by Palmgreen with multiple linear regression as the data analysis tool. This type of research is explanatory research with a quantitative approach. The sampling technique used non probability sampling using purposive sampling. The population in the study were active students in Semarang City who accessed the @FWBESS Twitter account and actively communicated with their friends about sex. The results of the study of 141 respondents showed that there was a positive influence between the intensity of accessing the @FWBESS Twitter account and the intensity of communication between friends about sex towards the level of acceptance of premarital sex. The variety of information on the @FWBESS Twitter account is one of the reasons why premarital sexual behavior can be accepted by respondents. Communication with friends about sex also has an influence in shaping the acceptance of respondents' premarital sex. The absence of binding rules in communicating with friends causes the content of discussions to vary, one of which discusses sex.